Free will, robots, and the axiom of choice - Schuhr, Jan C. (Paper series. Series C, Bioethics/medicine/technology/environment World Congress of Philosophy of Law and Social Philosophy, 2012)
There are quite a number of similarities between the moral concept of choice and the mathematical axiom of choice. These similarities shed light on how to adapt law to solve cases that arise with the increasing “autonomy” of robots